REVIEW: PELUANG REKAYASA PROSES PENGOLAHAN DAN DIVERSIFIKASI AMPING BERAS SEBAGAI PRODUK UNGGULAN DAERAH KABUPATEN SAMBAS - Rozana (Jurnal Agroindustri Pangan, 2022)
The quality of the amping of rice is still low, has a dull color, not thin enough so that the texture is hard, and there is still a lot of mixture of husks and black rice. In addition, to be able to enjoy rice amping, consumers must prepare other additional ingredients such as grated coconut with brown sugar, so the practical level of the product it still needs to be improved and consumers can immediately enjoy rice amping products easily and practically. Improvements in the quality of Amping Sambas products need to be carried out through improving processing processes and diversifying rice amping products in accordance with current trends in the market. Improvements to the process of making Amping Sambas can refer to existing processes, among others, by paying attention to the raw materials for manufacture, using rice from varieties that have moderate amylose content (20-25%), soaking at room temperature for 7-8 hours, doing roasting is carried out at a temperature of 302 oC for 41 seconds, and the flattening is carried out in 2 stages, stage 1 at 45 oC, stage 2 at roller pressure of 145 ± 5 kg/cm2 and a temperature of 75 ± 5 oC. to increase consumer acceptance of Amping Sambas products, diversify products, including in the form of Iron Fortified Chocolate Flavored Rice Flakes, Roasted Rice Flakes in Cereal Bars, and Cereal Bars Made from Glutinous Rice Flakes and Sunnah Foods.